2007
DOI: 10.1002/cncr.22841
|View full text |Cite
|
Sign up to set email alerts
|

Primary diffuse large B‐cell lymphoma of the tonsil

Abstract: The combination of palladium complex (tBu3P)Pd(Me)Cl (1) and NaB[3,5‐(CF3)2C6H3]4 (NaBAr4) catalyzed homopolymerization of a novel monomer, norbornene (NB) with a pendent 2‐fluorosulfonyltetrafluoroethoxymethyl chain (NBSF). Catalytic activities of 1/NaBAr4 were higher than those of previously reported palladium or nickel catalysts, probably, because the palladium center with electron donative tBu3P ligand was barely poisoned by the sulfonyl fluoride coordination. Thus, 1/NaBAr4 is the current best catalyst sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 25 publications
1
35
0
2
Order By: Relevance
“…With regard to tonsillar lymphoma, a few studies have reported that higher radiation doses result in better local control and overall survival (OS). However, the therapeutic effects of RT and the optimal RT dose require further evaluation with respect to tonsillar lymphoma [2,13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…With regard to tonsillar lymphoma, a few studies have reported that higher radiation doses result in better local control and overall survival (OS). However, the therapeutic effects of RT and the optimal RT dose require further evaluation with respect to tonsillar lymphoma [2,13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…Примарни тонзиларни лимфом чини мање од 1% малигнитета главе и врата;. NHL усне шупљине и орофарингса чине 13% свих примарних екстранодалних NHL 3,4 . Већина тонзиларних лимфома је пореклом B-ћелија и дифузни великоћелијски B-лимфом је најчешћи 67%-96%, следи MCL са 10%.…”
Section: уводunclassified
“…Већина ових пацијената има локализовану болест 6,7,8,9 , стадијум 1 или 2. Код пацијената са раним стадијумом болести без обимних маса, петогодишње преживљавање је 65%-85% 3,8,10,11 . Успех лечења зависи од откривања болести управо у раним стадијумима.…”
Section: уводunclassified
“…High levels of local control and favorable survival can be achieved for patients with localized WR-DLBCL using combined modality therapy (11,(15)(16)(17). However, the role of consolidation radiotherapy for specific cohorts of DLBCL patients is controversial because of radiotherapy-related, late side-effects (15,(18)(19)(20).…”
mentioning
confidence: 98%